Immunotherapy for older patients with melanoma: From darkness to light?. (18th August 2020) - Iacono, Donatella; Vitale, Maria Grazia; Basile, Debora; Pelizzari, Giacomo; Cinausero, Marika; Poletto, Elena; Pascoletti, Gaetano; Minisini, Alessandro Marco
Abstract: Approximately 40% of malignant melanomas are diagnosed in patients older than 65 years. Elderly patients with melanoma present clinicopathological features related to a more aggressive biology, and they are often diagnosed with advanced stage of disease. Interestingly, in older patients the immune system can be altered with changes both in the innate system and in the adaptive immune system with the acquisition of a pro‐inflammatory and immune suppressive phenotype. Immunotherapy with immune checkpoint inhibitors has reshaped the treatment strategies and prognosis of patients with melanoma, and particularly, older age should not be considered a contraindication for immunotherapy. However, data regarding efficacy and safety of immunotherapy in elderly population are still limited because frail older patients are generally excluded from clinical trials. Recently, real‐world data have shed light on similar efficacy and safety of immunotherapy in older population compared with younger counterpart. The aim of the present review was to summarize the available knowledge on the underlying immune system in older patients with a diagnosis of melanoma and the immunotherapeutic approaches in this population.